Biodiesel Production From Palm Oil Mill Effluent (Sludge) - Isa, Faezah (Universiti Teknologi PETRONAS, 2009)
Biodiesel which is also defined as alkyl-esters is produced from vegetable or animal oil through transesterification process. In this process, triglycerides contained inside the vegetable oil will react with alcohol to form alkyl-esters. Currently, the biodiesel plants in especially in Malaysia produce biodiesel from refined bleached de-odorized palm oil (RBDPO). As a result, the economical profits that can be obtained is greatly reduced as the cost of production is spread across four aspects, extraction of palm oil from palm fruits to become crude palm oil (CPO), refining it to become RBDPO, treating it with alcohols to become FAME, and further refining it to become biodiesel. This research is conducted to observe the possibility of palm oil effluent sludge (POME) into biodiesel. Palm oil refinery in Malaysia produces ton ofeffluent per day which can be converted to useful energy. The research begins by extensive literature review about biodiesel and also about the extraction of long chain fatty acid (LCFA) in effluent sludge. There are two types ofsludge used which is sludge oil from sludge bin and sludge water from pond that was undergo aerobic digestion. One ofthe ways to extract oil is by using adsorbent such as zeolites and activated carbon. In normal atmosphere condition, sample is stirred at 200 rpm for 10 minutes and then extracted using petroleum ether. Another method is by using sample ofsludge oil which being heated at 100 °C. Then, continued by filtration process to sieve the solid that diluted in the oil. Biodiesel process is conducted at 60 °C by using methanol and acid sulphuric as catalyst. Then, Free Fatty Acid (FFA) analysis and thin Layer Chromatography (TLC) to observe biodiesel produced.